Does successful treatment of overactive bladder improve co‐morbidities in patients with nocturia?. (13th March 2019) - Chin, Kai Sin; Rose, Georgie E.; Ervin, Claire F.; Ong, Tee Juan; Whishaw, David M.; Bower, Wendy F.
Abstract : Objective: To investigate whether treatment of overactive bladder (OAB), one comorbidity of nocturia, could reduce waking to void and improve other co‐existing symptoms. Methods: A prospective cohort study was conducted at Royal Melbourne Hospital. Participants received 12 weeks of standard treatment, including lifestyle interventions and pharmacotherapy. Outcome measures were nocturia episodes, severity of urinary urgency/incontinence, sleep quality, daytime somnolence, anxiety and depression scores, quality of life and change in blood pressure. Results: Twenty participants completed the study. Nocturia frequency improved by one void per night. Overactive Bladder Symptom Score, sleep quality, first uninterrupted sleep time and systolic blood pressures improved. There were no significant changes in daytime somnolence, mood or quality of life. Conclusions: In this pilot study, nocturia and other co‐morbid dysfunctions appeared to improve when the severity of OAB was reduced. Treatment of OAB co‐morbid with nocturia reduces urinary symptoms and may improve sleep parameters and positively impact return to health.